Determinants of environmental disclosure in the oil palm industry in Malaysia - Mojilis, Frederica (Curtin University, 2013)
The study examines the determinants of environmental disclosure in the oil palm industry in Malaysia. It applies Ullmann’s (1985) three-dimensional stakeholder model to observe the association of stakeholder power, strategic posture and economic performance with environmental disclosure. Disclosure is shown to be low overall, with significant differences between oil palm and other companies. The study confirms the robustness of Ullmann’s model in predicting environmental disclosure and suggests a role for government in its regulation.